A research agenda for global environmental politics - Dauvergne, Peter; Alger, Justin (Elgar research agendas., 2018)
"In a world confronted with escalating environmental crises, are academics asking the right questions and advocating the best solutions? This Research Agenda paves the way for new and established scholars in the field, identifying the significant gaps in research and emerging issues for future generations in global environmental politics. From an analysis of state and non-state environmental governance to the politics of climate change, food sustainability, forests and oceans, the preeminent academics and leading researchers take an important step in establishing an agenda for the future trajectory of research. Split into three sections - global environmental governance, the politics of environmental problems, and engaged research and scholar activism - chapters discuss the most influential steps in recent environmental and political studies and offer original perspectives on the future trends. Inspiring the next generation of academics and activists, this Research Agenda provides excellent guidance for graduate students and supervisors looking for the most innovative and pressing research questions in environmental politics."--Page 4 of cover.